PENGARUH KUALITAS PELAYANAN DAN KELENGKAPAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT NG TECH SUPPLIES - Liliana, Trisna; Evyanto, Winda (LPPM Universitas Putera Batam, 2022)
In this era of covid-19, the competition in the business world is getting tougher along withthe times and increasingly sophisticated technology. So that makes the company muststrive and struggle to maintain its business so that its existence is accepted by consumersin the Indonesian market, where each company will continue to innovate and strive toprovide the best quality in meeting customer desires This research is to determine theeffect of service quality, completeness product to purchase decisions at PT Ng TechSupplies.This reseach using method quantitative approach. And in this reseach the totalpopulation were 118 consumers, using simple random sampling technique and using theSlovin formula. Then the data uses a questionnaire whose results will be tested using theSPSS version 25 application. The test results obtained are the service quality variable hasa significant influence on purchase decisions with sig 0.921 <0.05, then the completenessproduct variable has a significant influence on purchase decisions with sig 0.000 < 0.05,and service quality, completeness product simultaneously have a positive and significanteffect on consumer satisfaction with sig 0.000 < 0.05.